Kenyan Nurses Involvement in National Policy Development Processes - Pamela Atieno Juma; Nancy Edwards; Denise Spitzer (Nursing Research and Practice)
The aim of this study was to critically examine how nurses have been involved in national policy processes in the Kenyan health sector. The paper reports qualitative results from a larger mixed method study. National nonnursing decision-makers and nurse leaders, and provincial managers as well as frontline nurse managers from two Kenyan districts were purposefully selected for interviews. Interviews dealt with nurses’ involvement in national policy processes, factors hindering nurses’ engagement in policy processes, and ways to enhance nurses’ involvement in policy processes. Critical theory and feminist perspectives guided the study process. Content analysis of data was conducted. Findings revealed that nurses’ involvement in policy processes in Kenya was limited. Only a few nurse leaders were involved in national policy committees as a result of their positions in the sector. Critical analysis of the findings revealed that hierarchies and structural factors as well as nursing professional issues were the primary barriers constraining nurses’ involvement in policy processes. Thus, there is need to address these factors both by nurses themselves and by nonnursing decision makers, in order to enhance nurses engagement in policy making and further the contribution to quality of services to the communities.